Dakwah Bil Maal Badan Amil Zakat Nasional Kota Lubuk Linggau Melalui Pengentasan Kemiskinan - Ratu, Liliany Purnama; Ikit, Ikit; Dores, Dedi; Bakrin, Bakrin; Sumarni, Buana (STAI Bumi Silampari, 2024)
Da'wah bil maal means the activity of calling on people to have other people's rights in the property they own. The rights of other people such as the needy and poor, building mosques, building hospitals, educational institutions, humanitarian institutions. Qualitative descriptive research means that the study focuses on problem with the existing data, analyzes the data and draws conclusion at the end. The sample was chosen by purpossive sampling method by selecting informants who met the criteria, including preachers, BAZNAS leaders, BAZNAS employees and the community. Observation, interviews and documentation were used to collect the data. Meanwhile, trigulation is used to analyze the data;data reduction, data display and verification or draw conclusions.The research result showed that BAZNAS bil maal da'wah are aimed at the citizen interest is both building religious facilities and building educational institutions. Preaching by inviting people to give wealth (zakat, infaq, alms). The concept of this activity emphasizes the wealth used. BAZNAS bil maal da'wah is the spearhead for alleviating poverty. BAZNAS Lubuklinggau City in alleviating poverty can be seen from the strategy for collecting and distributing funds. BAZNAS fund collection carries out various innovations, collaborating with all parties (government, BUMN, entrepreneurs). Meanwhile, the distribution of zakat funds must be launched so that it is effective, efficient and on target. In distributing funds, BAZNAS has programs, namely economic programs, education programs, health programs, da'wah programs and humanitarian programs. The obstacles faced by BAZNAS Lubuklinggau City in alleviating poverty are limited operational funds, public awareness in paying zakat, public awareness in using zakat funds, the society has has strustless on Zakat institutions, zakat administrators still do not understand zakat governance.